Mechanisms of carbon distribution and stability in the photosynthetic processes of plant-soil systems influenced by arbuscular mycorrhizal fungi during reclamation of mining areas - Yinli BI; Ke ZHANG; Li XIAO; Dongdong WANG (Meitan xuebao)
Inoculation of Arbuscular Mycorrhizal Fungi (AMF) combined with vegetation restoration has become a key reclamation technology for ecological restoration in mining subsidence. Investigating the accumulation and distribution of photosynthetic carbon sequestration within the plant-soil system following years of mycorrhizal restoration holds significant importance for elucidating the carbon cycling processes in reclaimed soils of mining regions and achieving effective carbon sequestration. The distribution strategy of photosynthetic carbon in the plant-soil system under long-term mycorrhizal cultivation was studied in the AMF area and the control area of Daliuta Mycorrhizal bioreclamation experimental demonstration area by 13C isotope pulse labeling method and metabolic. The results are summarized as follows: Following leaf carbon sequestration, there was a downward transfer of carbon to the leaf, stem, root, and soil. Long-term mycorrhizal restoration significantly enhanced the accumulation of photosynthetic carbon within the plant-soil system in the mining area. The average photosynthetic carbon enrichment amount in the labeled AMF area was 1.33 times greater than that observed in the labeled control area. Additionally, the distribution ratio of photosynthetic carbon to the underground (plant roots and soil) was increased by inoculation, and the distribution ratio and average enrichment in the underground part of the labeled inoculation area were 13.4% and 299.3% higher than those in the labeled control area. More photosynthetic carbon 13C was present in the form of mineral-bound organic carbon(MAOC) after entering the soil. The average enrichment amount of photosynthetic carbon 13C in MAOC was 246.8% more than that in the labeled control area. Furthermore, mycorrhiza improved the ability of soil organic carbon conversion and the net enrichment of 13C-MBC in the labeled AMF area was 4.5 times that in the labeled control area, thereby contributing to soil carbon stability. Meanwhile, mycorrhizal associations enhance soil organic carbon conversion efficiency, facilitating the retention of photosynthetic carbon within the soil. Combined with the results of metabolomics, it was found that AMF mycelial network affected the carbon metabolism pathway of tyrosine metabolism, glycolysis and glycolysis synthesis, amino acid and nucleotide sugars synthesis respectively. This regulation occurred through the metabolism of lipid and lipid molecules, organic heterocyclic compounds, organic oxides, phenylpropane and polyketones, ultimately affecting the enrichment of photo-synthetic carbon 13C in soil and the stability of organic carbon pool. In general, microbial mycorrhizal reclamation can not only promote the accumulation of soil organic carbon pool, but also regulate the transformation and stability of organic carbon pool, which is one of the most effective methods to accelerate the realization of carbon reduction and carbon sink increase in mining area.